ESRA19-0686 'Don't GA(S) me now!': Using a combined paravertebral and pecto-intercostal fascial plane block for awake breast surgery to reduce post-operative morbidity. (30th August 2019) - Zaky, M; Ko, S; Pawa, A
Abstract : Background and aims: Combined thoracic paravertebral and pectoral nerve blocks has been cited 1 2, 3 4 as an effective technique for breast surgery. We present a case of a high-risk ASA 4 patient who successfully underwent surgery with regional anaesthesia and conscious sedation. A 61 year old female requiring mastectomy and axillary lymph node clearance due to left breast carcinoma. Significant medical background of chronic hypoxia and right heart failure on home oxygen as a result of interstitial lung disease and emphysema. Multidisciplinary team agreement to avoid general anaesthesia due to high risk of respiratory complications and death. Methods: Regional anaesthesia performed after sedation with low-dose midazolam and fentanyl. Paravertebral block undertaken using real-time ultrasound scan with 20ml of solution containing 10ml 2% lidocaine with 1/200, 000 adrenaline and 10ml 0.5% levobupivacaine. Following this, PECS II block was sited using 30ml of solution containing 10ml 1% lidocaine with 1/200, 000 adrenaline, 10ml 0.25% levobupivacaine and 10ml 0.9% saline. 5ml 1% lidocaine was administered for the pecto-intercostal fascial block (PIFB). Results: Intra-operatively, conscious sedation with propofol target controlled infusion. Only a total of 50mcg fentanyl required throughout as supplemental analgesia. Good post-operative pain control achieved with single dose of dihydrocodeine and regular oral paracetamol and ibuprofen. Patient discharged after 48 hours of level 1 care. Conclusions: We have demonstrated the feasibility of using regional anaesthesia for achieving good result for breast surgery with axillary lymph clearance. Wider utilisation of this can effectively avoid similar patients needing ICU admissions, reducing financial burden and potential peri-operative complications that might have resulted from general anaesthesia.